(untitled) (Baltimore, 1998)
The book takes into account recent developments in international agricultural development, especially as these affected the role of the state, markets, and other institutions in development. The authors deal with topics such as market failures, food insecurity, rural poverty, environmental degradation, income and asset inequality, fiscally sustainable organizations, the changing roles of the public and private sector in research, and input and output marketing systems.
Keywords: Agriculture,Nông nghiệp,Agricultural development projects,Dự án phát triển nông nghiệp; Economic aspects,Các khía cạnh kinh tế; Developing countries,Các nước đang phát triển